Meningkatkan Kemampuan Motorik Halus Dengan Membuat Gantungan Kunci Anak Usia 5-6 Tahun - Qorina Widadiyah; Muhammadun; Euis Farina Endah (STAI Siliwangi Bandung, 2022)
The research was carried out because the children could not align eye observations with hand movements, the limited media used by the teacher in play activities, and the lack of training related to fine motor activities. This study aims to determine the results of fine motor development through playing making key chains. Researchers used classroom action research methods with 13 children aged 5-6 years, using data collection techniques by observation, documentation and interviews. Observations of the first cycle, stated that children with criteria for starting to develop there were 4 percentages of 30.76%. The criteria for developing according to expectations are 4 percentages 30.76%, the criteria for developing very well 5, the percentage is 38.46%. Cycle II stated that of the 13 children who started to develop, there was 1 with a percentage of 7.69%. Developing Criteria According to Expectations 5, the percentage is 38.46%. Criteria for Very Good Development 7, the percentage is 53.84%. Reports on the results of cycles 1 and 2 stated that children experienced an increase in their fine motor skills with a percentage of 20% better than their pre-cycle.